Mentoring as an Interaction Ritual: Generating Emotional Energy and Solidarity among Urban Mosque Youth - Najwa Adila Pertiwi; Ahmad Shabbir (Jurnal Ilmu Sosial Indonesia (JISI), 2026)
Urban landscapes are frequently characterized by heightened individualism and the erosion of traditional social cohesion. Conversely, certain religious collectives effectively maintain robust social bonds through consistent, routine engagement. This research investigates mentoring practices within the Kumpulan Remaja Masjid An-Nahl (KURMA) in BSD City, addressing a significant scholarly void: the tendency to prioritize large-scale, event-based religious activities over the subtle, micro-interactional dynamics of daily routines. Utilizing a qualitative case study framework, data were synthesized from participant observation and semi-structured interviews with 2 mentors, 6 administrators, and 2 members. Grounded in Randall Collins’ Interaction Ritual Chains (IRC) theory, the analysis demonstrates that mentoring functions as a recurring interaction ritual that generates emotional energy (EE) and bolsters group solidarity. This accumulated EE not only encourages long-term participation but is also encoded into group symbols, including internal jargon and a distinctive three-finger hand gesture signifying collective identity. Ultimately, this research underscores that solidarity in urban mosque youth groups is a product of emotionally resonant routine interactions rather than transient religious events.